Obesity and depression, an analytical study among adults attending primary care clinics in Bahrain - Ali, Afaf A. M.; Alalwan, Naseem F.; Ali, Mona A. M.; Alsayyad, Adel S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Both depression and obesity are widely spread problems with major public health implications. Obesity is a major risk factor for several chronic diseases. However, its consequences on mental health is less certain. This study explore the association between obesity and depression among adults in Bahrain. Methods: A cross sectional study was conducted among adults ≥18 years attending general practice in four primary care health centers that have been selected randomly from the four governorate in Bahrain. Self-filled questionnaire that includes demographic information, depression scale and other behavioral and clinical factors were used as the study tool. Weight and height were measured for each participant and BMI was used to assess obesity. Depression was assessed using beck depression inventory scale, with a score of more than 16 to indicate clinical depression. Results: The prevalence of depression is 16% while the prevalence of obesity is 42% among adults in the study. The prevalence of depression among underweight, normal weight, overweight and obese adults are almost the same (around 16%). Analysis using Chi Square test and regression analysis test showed no significant association between obesity and depression. Conclusions: The present study did not confirm any relationship between obesity and depression among adults attending primary care clinics in Bahrain.